The Analysis of the Readability Levels of The Reading Texts in Textbook Entitled “Fast Tract to English” for the Third Year Students of SMA Based on Raygor Readability Estimate - Yeli Nurhamsih (Universitas Jambi, Magister Program of English Education Department, 2017)
The objectives of this research are to know the readability levels of the reading texts in the textbook and want to know whether or not the reading texts are suitable linguistically for the third year students of SMA. The method used in writing this research was the descriptive method. There were the 38 reading texts analyzed which were taken from an English textbook entitled “Fast Tract to English”. The data were collected through the documentation technique. Those reading texts were analyzed by using Raygor Readability Estimate. There are five findings in this research. First, on the whole, the readability of the textbook is 11. It means the textbook is not suitable lingustically for the third year students of SMA because in general, the students have been studying English for nine years. Second, the writer found four reading texts that their readability levels are under Level 9. Based on Raygor Readability Estimate (RRE), those reading texts are not suitable linguistically for the third year students of SMA because they are predicted as too easy texts for them. Conversely, those reading texts can be linguistically suitable for those who have been studying English since first year of Junior High School or for less than 9 years. Third, there are seven reading texts that are considered as readable texts. The readability level of those reading texts is 9. Based on RRE, those texts are suitable linguistically for the third year students of SMA because level 9 is predicted as suitable readability level for them. However, those texts cannot be suitable linguistically for them if they have been studying English for under or over nine years. Fourth, most of the readability levels of the reading texts in the textbook are over Level 9 namely twenty-six reading texts. Based on (RRE), those reading texts are not linguistically suitable for the students who have been studying English since they were in fourth grade of Elementary school. Those reading texts can be suitable linguistically for those who have been studying English formally for over nine years. Fifth, among 38 reading texts, there is only one reading text that its readability level is in Invalid Level. This text is considered as not readable text. It means, this text cannot be read and learnt. It is predicted, the students might have difficulties in understanding this reading text. The reading text entitled “Non-Aligned Movement”. Keywords: Readability Levels, Reading Texts, Textbook.